Psicanálise, antropologia e alteridade: apontamentos para um debate - SOUZA, Maurício Rodrigues de (2014)
This work privileges the subject of otherness, taking it as a theme for a dialogue between psychoanalysis and anthropology. Therefore, after some considerations about the notion of strangeness in the work of Freud, it emphasizes the idea that the difference imposed by the unconscious owns a narrative and an individual temporality that refuse to obey the principles of representational thought. Because of that the strangeness and the negativeness of the analytic encounter become places of possibility, amplifying the concept of otherness and the capacities of interpretation, now placed in a mid-point between the production of sense and the experience of emptiness. That's the lesson of non-lesson proposed by this uncanny other of the unconscious to anthropology and, in a larger scale, to the social sciences: to admit the possibility of sense, but not necessarily its ending, offering a less compromised expression to a stranger that is now irreducible to pre-established set codes.